Development of a Decision Support System Evaluation of Lecturer Learning Processes Using the Scoring System Method at IKIP PGRI Semarang - Much. Rosul; Munifah Munifah (Lembaga Pengembangan Kinerja Dosen, 2021)
The activity of evaluating the learning process of lecturers by students is one of the supporting efforts to improve the quality of the learning process of lecturers in each university. IKIP PGRI Semarang conducts evaluation activities for the learning process of lecturers by students every semester, but the number of students who conduct evaluations is still limited to only twenty students for one lecturer and the process of implementing evaluation activities and archiving evaluation data is inefficient because it requires less time and money and not effective because it still uses a semi-manual system, namely by distributing questionnaires and processing evaluation results using Microsoft Excel so that there are two processes, namely input of assessment data by students and input of data processing evaluation results. This study aims to develop an evaluation system for the learning process of lecturers by students that is more effective and efficient with the data obtained more quickly, is representative and supports the completeness of the validity of the data so that it can help make decisions from the results of the evaluation process. The results of this study are in the form of applications and evaluation results of the lecturer's learning process by students with a web-based scoring system method using LAMP (Linux Apache MySql PHP) which is integrated with academic information system data.